2013
DOI: 10.1080/07448481.2013.769260
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Assault Reporting Procedures at Ohio Colleges

Abstract: Many colleges are failing to offer basic reporting options to victims of sexual assault. Having a clearly labeled sexual assault policy on a campus Web site that includes 24/7 reporting options and defines acts of sexual assault can aid victims in the reporting process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 12 publications
1
44
0
Order By: Relevance
“…Studies have shown that, to date, campus administrators' efforts to provide information about critical definitions and information about sexual assault resources and the procedures available to students are uneven (Karjane et al, 2002;Krivoshey et al, 2013). In one study, 33 percent of a sample of 60 universities offered students "poor" information about sexual violence on their websites (Hayes-Smith and Hayes-Smith,2009).…”
Section: Campus Resources and Students' Knowledge Of Themmentioning
confidence: 99%
“…Studies have shown that, to date, campus administrators' efforts to provide information about critical definitions and information about sexual assault resources and the procedures available to students are uneven (Karjane et al, 2002;Krivoshey et al, 2013). In one study, 33 percent of a sample of 60 universities offered students "poor" information about sexual violence on their websites (Hayes-Smith and Hayes-Smith,2009).…”
Section: Campus Resources and Students' Knowledge Of Themmentioning
confidence: 99%
“…Few studies have focused on the definitions of "sexual assault/misconduct" as institutionalized in student codes of conduct (Hayes-Smith and Hayes-Smith, 2009;Karjane, Fisher, and Cullen, 2002;Krivoshey et al, 2013;Potter, Krider, and McMahon, 2000). All have employed some sort of content analysis of official publications, print-or Web-based.…”
Section: Institutional Definitions Of Sexual Assaultmentioning
confidence: 99%
“…Like Krivoshey et al (2013), a student assistant and I secured them via internet searches of institution's websites. 6 Initially, we sought the annual security report and student handbook (for the conduct code).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations